Benzofuranyl Esters: Synthesis, Crystal Structure Determination, Antimicrobial and Antioxidant Activities - C. S., Chidan Kumar; Li, Yee Then; Tze, Shyang Chia; Chandraju, Siddegowda; Win, Yip Foo; Sulaiman, Shaida Fariza; Hashim, Nurul Shafiqah; Kheng, Leong Ooi; Ching, Kheng Quah; Fun, Hoong Kun (MDPI, 2015)
A series of five new 2‐(1‐benzofuran‐2‐yl)‐2‐oxoethyl 4-(un/substituted)benzoates 4(a–e), with the general formula of C8H5O(C=O)CH2O(C=O)C6H4X, X = H, Cl, CH3, OCH3 or NO2, was synthesized in high purity and good yield under mild conditions. The synthesized products 4(a–e) were characterized by FTIR, 1H-, 13C- and 1H-13C HMQC NMR spectroscopic analysis and their 3D structures were confirmed by single-crystal X-ray diffraction studies. These compounds were screened for their antimicrobial and antioxidant activities. The tested compounds showed antimicrobial ability in the order of 4b < 4a < 4c < 4d < 4e and the highest potency with minimum inhibition concentration (MIC) value of 125 μg/mL was observed for 4e. The results of antioxidant activities revealed the highest activity for compound 4e (32.62% ± 1.34%) in diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, 4d (31.01% ± 4.35%) in ferric reducing antioxidant power (FRAP) assay and 4a (27.11% ± 1.06%) in metal chelating (MC) activity.